2020
DOI: 10.4103/iju.iju_116_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of extracorporeal shockwave lithotripsy and retrograde intrarenal surgery in the treatment of renal pelvic and proximal ureteral stones ≤2 cm in children

Abstract: Introduction: We aimed to compare extracorporeal shockwave lithotripsy (ESWL) and retrograde intrarenal surgery (RIRS) in pediatric patients with ≤2 cm renal pelvis and proximal ureteral stones. Methods: Medical records of 165 pediatric patients who underwent shockwave lithotripsy (SWL) or RIRS for upper urinary system stones up to 2 cm between January 2014 and December 2018 were retrospectively reviewed. After exclusions, the remaining 130 patients included 73 in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The study sample sizes ranged from as low as 43 AME ( 19 ) to as high as 212 AME ( 17 ). These samples were drawn from diverse regions, including Turkey ( 20 , 24 , 26 - 28 ), Italy ( 21 ), Egypt ( 18 , 19 , 22 ), France ( 23 ), Poland ( 25 ), India ( 17 ), and China ( 29 ). The mean age of the participants varied significantly across the studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study sample sizes ranged from as low as 43 AME ( 19 ) to as high as 212 AME ( 17 ). These samples were drawn from diverse regions, including Turkey ( 20 , 24 , 26 - 28 ), Italy ( 21 ), Egypt ( 18 , 19 , 22 ), France ( 23 ), Poland ( 25 ), India ( 17 ), and China ( 29 ). The mean age of the participants varied significantly across the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The youngest mean age was reported to be 2.4±1.3 years ( 18 ). Some studies reported mean ages for different groups, showing variability within their samples ( 19 , 20 , 22 - 24 , 26 - 28 ). Gender distribution, where specified, was skewed towards males in all studies ( 17 - 22 , 24 - 27 , 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We read the article by Guler et al . [ 1 ] with interest and appreciate the authors for providing insight toward the role of extracorporeal shockwaves lithotripsy (ESWL) and retrograde intrarenal surgery (RIRS) in pediatric urolithiasis through a comparative trial. However, we have the following observations.…”
mentioning
confidence: 99%